Complete Sequence of the IncT-Type Plasmid pT-OXA-181 Carrying the bla(OXA-181) Carbapenemase Gene from Citrobacter freundii - Villa, Laura (American Society for Microbiology, 2013)
The gene encoding the carbapenemase OXA-181 (an OXA-48 variant) was identified from a Citrobacter freundii isolate coproducing NDM-1. The whole sequence of plasmid pT-OXA-181 bearing the bla(OXA-181) gene was determined and revealed a 84-kb mobilizable but non-self-conjugative IncT-type plasmid. It totally differs from the 7.6-kb ColE-type and bla(OXA-181)-bearing plasmid recently identified in a Klebsiella pneumoniae isolate. However, in both plasmids, insertion sequence ISEcp1 might have played a role in acquisition of the bla(OXA-181) gene.